Historical Evolution and Cultural Significance of Nabahī in Kathmandu - Basukala, Junu Maiya (Journal of Buddhist Studies (T.U.), 2025)
Nabahī is one of the sixteen Bahīs in Kathamandu Metropolitan City, located Ward No. 23 at Ombahal. It was constructed during Malla period and its historically associated with the Shakya community. Even though its prominence, the exact date of its establishment, the identity of its founder, and its historical events, cultural activities, and characteristics remain unknown. This paper aims to examine the founder historical development, features, and cultural practices of Nabahī. The study employs a qualitative research design, focusing on human activities and relevant primary sources such as inscriptions. By offering a comprehensive analysis of these sources, the paper provides rich historical context about Nabahī. The findings suggest that the original name of the Bahī was Khoitānaka, and its foundation, evolution, and cultural activities closely mirror those of other vihāras and Bahīs. Furthermore, the current condition of Nabahī deviates from traditional Bahī vāstuśāstra as outlined in the vāstuśāstra.